Geochemistry, Hydrothermal alteration and Ore mineralogy of Skarn Mineralization at Wethey-Pheshey area, Thabeikkyin Township, Mandalay Region, Myanmar - Toe Naing Oo; Lucas Donny Setijadji; I Wayan Warmada; Than Than Oo (Journal of Applied Geology, 2016)
Wethey-Pheshy area is located 80 km north of Mandalay at Thabeikkyin Township, Mandalay Region. X-ray Diffraction (XRD) Analysis and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) were applied in this study. Geochemical studies on the host rocks indicate that major and minor oxides compositions of metamorphicrocks show some degree of variation. CaO, MgO, FeO, TiO2 and P2O5 concentration of the metamorphic rock samples show a coherent negative correlation with SiO2 whereas Na2O is positively correlated with SiO2. The metamorphic rocks are strongly enriched in light rare earth elements (LREE) and relatively depleted in heavy rare earth element (HREE). The depleted Eu-nomalies in the chondrite-normalized REE diagrams indicate a plagioclase-depleted Eu crustal source or fractionation during magmatic differentiation. Intrusion of granitic rocks in the diopside marble caused the base metal ore mineralization and associated skarn alterations. Granite shows the sub-alkaline nature and peraluminous character. It is identified as I-type granite (magnetite series) developed in the volcanic arc setting. Hydrothermal alteration types associated with gold and skarn mineralization in the study area include calc-silicate alteration, propylitization, sericitization (argillitization) and hematization. Based on the nature and characteristics of host rocks, mineralization and alteration style and geochemical characteristics in the study area is identified as intrusion-related skarn mineralization. Common ore minerals include chalcopyrite, galena, sphalerite, pyrite, gold and Fe-oxides.